How to link: Plasmid Curing and Lead Tolerance Ability of Pediococcus pentosaceus - Fadhil Neamah Al-Kanany; Raghad Shubbar Jaafar (Journal of Tropical Biodiversity and Biotechnology, 2022)
Pediococcus pentosaceus has a high level of resistance to heavy metals, making it one of the biological alternatives for dealing with heavy metal contamination in the environment. The current study sought to identify the genetic factors responsible for this ability by curing the plasmid of these bacteria using various curing agents (Acridine orange and Sodium Dodecyl Sulfate). The findings demonstrate that both curing agents had perfect curing ability. The bacteria were able to tolerate a wide range of Lead concentrations (50-2000 ppm). This capacity was reduced when the plasmid was removed, but it did not disappear, implying additional resistance genes on the chromosomes. The antibiotic susceptibility observations supported the significance of plasmid genes in lead resistance ability, the findings revealed differences in the pattern of antibiotic resistance between wild and cure plasmid bacteria, the wild one had different antibiotic MIC values for Nitrofurantoin and Trimethoprim/Sulfamethoxazole (<=16 and <=10 µg/ml) respectively), on the other hand for the same antibiotics, the MIC results for plasmid-cured bacteria were 64 and 80 g/ml. Based on the findings, we can conclude that plasmid genes play a significant role in Pediococcus pentosaceus to resist lead, and there is a strong correlation between antibiotic resistance and lead resistance.